The economics of religion anthropological approaches - Obadia, Lionel; Wood, Donald C. (Bingley, U.K. : Emerald, 2011)
The Economics of Religion explores the new paradigms of'religious economics' and'economies of religion' under the scope of transdisciplinary and international perspectives. It examines and appraises some of the recent theoretical developments and methodological innovations in religious and social sciences. This volume offers the chance to extend the analysis of religious behaviours by means of conceptual and methodological models of economics. It goes far beyond the classical'economy and religion' debate, and suggests not only theoretical but also epistemological changes in the study of religion: individual rationality and rational choice, market theory, demand and supply theory, branding and commodification of religion, believers'consumer' habits, churches competitive strategies, for example. Of course, these are not exempt from criticism, which this volume also addresses. These detailed and localized case-studies range from experimental to ethnographic methods, psychological to cultural aspects of believing and practising cults in the scope of economics of religion. Geographical areas covered include Nigeria, Bolivia, Italy, Mexico, France, Korea, Nepal and Tonga.
Economics and religion, economics in religion, economics of religion : reopening the grounds for anthropology? / Lionel Obadia, Donald C. Wood -- Trust, faith and calculativeness : a theoretical extension of O. Williamson's'institutional trust' / Peter Seele -- Property unbound? : debating the'sacrificial economy' / Simon Coleman -- A Catholic alternative to globalization? : the Compagnia delle Opere / Riccardo Nanini -- The economy of the host in the monastic world : a non-economic economy / Isabelle Jonveaux -- Is Buddhism like a hamburger? : Buddhism and the market economy in a globalized world / Lionel Obadia -- Spiritual capital : on the materiality and immateriality of blessings in Puerto Rican Brujer / Raquel Romberg -- Promising and engaging the future through ritual sponsorships in eastern Yucatan, Mexico / Andr Dapuez, Andr Dzib May, Sabrina Gavigan -- God unlimited : economic transformations of contemporary Nigerian Pentecostalism / Asonzeh Ukah -- Multi-level marketing : at the crossroads of economy and religion / Nathalie Luca -- Economic, religious, and social practice of giving : a microanalysis of donating in the kingdom of Tonga / Natsuko Higa -- Are religious individuals more generous, trusting, and cooperative? : an experimental test of the effect of religion on prosociality / Brian Paciotti, Peter Richerson, Billy Baum, Mark Lubell, Tim Waring, Richard McElreath, Charles Efferson, Ed Edsten -- Charitable Christians, punitive neighbors : religiosity and economic norms in a water-scarce environment / Benjamin Jewell, Amber Wutich.
Keywords: Economics -- Religious aspects -- Islam; Religion -- Economic aspects